2018
DOI: 10.1093/jjco/hyy067
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of metastatic giant cell tumor of bone in the pre-denosumab era. A systematic review and a meta-analysis

Abstract: To our knowledge this is the first study to derive estimated pooled OS and DSS of mGCT based on a large dataset. SRs were not exceptional phenomena. In a long run the disease could impact in a significant way on the life expectancy of affected subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 66 publications
3
22
0
2
Order By: Relevance
“…In the present study, with the large cohort of malignant GCTB, the 5-year OS was 82.3% (95% CI: 77.9-86.6). This rate was consistent with the reported rate of 86.9% by Itkin et al [10] and 80% by Domovitov et al [12]. The prognostic factors were revealed, and poor survival was correlated with the following factors including age older than 34 years, higher T stage, distant tumor and the extraskeletal sites.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, with the large cohort of malignant GCTB, the 5-year OS was 82.3% (95% CI: 77.9-86.6). This rate was consistent with the reported rate of 86.9% by Itkin et al [10] and 80% by Domovitov et al [12]. The prognostic factors were revealed, and poor survival was correlated with the following factors including age older than 34 years, higher T stage, distant tumor and the extraskeletal sites.…”
Section: Discussionsupporting
confidence: 92%
“…But the issues were not intensively studied due to the lack of long-term followup clinical data [9]. Itkin and his colleagues retrospectively retrieved the data of 242 patients from 26 studies with a median follow-up of 6.9 years [10]. They reported an estimated overall survival rate of 86.9%.…”
Section: Introductionmentioning
confidence: 99%
“…(95% CI: 77.9-86.6). This rate was consistent with the rate of 86.9% reported by Itkin et al [10] and 80% reported by Domovitov et al [13]. Prognostic factors were identi ed, and poor survival was correlated with the following factors: age older than 34 years, high T stage, distant tumour stage and extraskeletal sites.…”
Section: Discussionsupporting
confidence: 91%
“…Pulmonary metastases are very rare and typically slow-growing. These are thought to represent pulmonary implants that result from embolization of intravascular growths of GCTB [33].…”
Section: Giant Cell Tumour Of Bonementioning
confidence: 99%